Pengaruh Penerapan Prinsip GCG, Komitmen Organisasi, Dan Budaya Tri Hita Karana Terhadap Kinerja Keuangan LPD - Utari, Ni Nengah Nari; Suartana, I Wayan (E-Jurnal Akuntansi, 2024)
The aim of the research is to obtain empirical evidence of the influence of GCG principles, organizational commitment and Tri Hita Karana culture on the financial performance of LPDs throughout Karangasem Regency. The population is 190 LPD in Karangasem Regency. The sampling technique is through purposive sampling. The number of samples is 20 LPDs with the Head of LPD and Supervisory Body as respondents. The data collection technique is by distributing questionnaires to 20 LPDs. The analysis technique is multiple linear regression analysis. The results of the analysis show that GCG principles, organizational commitment and THK culture have a positive effect on the financial performance of LPDs, which means that the increasing implementation of GCG, organizational commitment and THK culture will be able to improve the financial performance of LPDs throughout Karangasem Regency. The implication is that it becomes a guideline for consistently implementing GCG, organizational commitment and THK culture in LPD operations, so that financial performance increases, gains public trust and builds LPD in a positive direction. Keywords: Good Corporate Governance Principles, Organizational Commitment, Tri Hita Karana Culture, Financial Performance